Estimating Surface Current from HIMAWARI-8 SST Data using Particle Image Velocimetry Method (Case Study in The Flores Sea) - Kadek Setiya Wati; Takahiro Osawa; I Wayan Gede Astawa Karang (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Four High-Frequency radar systems (HF) have been installed in Indonesia to monitor surface currents. In-situ ocean current observations are relatively expensive and limited by spatial and temporal resolution. Satellite remote sensing enables the estimate of surface current data generally from surface tracer data, including sea surface temperature (SST). Various methodologies have been developed to obtain surface currents. With Himawari-8 SST data, this study examines the accuracy of the resulting estimation. The cross-correlation fields of two identical-sized interrogation windows obtained from sequential images are employed in Particle Image Velocimetry (PIV). The HF radar in Labuan Bajo was used to validate surface current velocity estimates. RMSE, bias, and the Willmott index determined the accuracy. According to the estimates of surface currents made on July 29, 2022, the results follow a monsoon characteristic wind pattern in the Flores Sea. HF radar observations better validate the V component current estimation than the U component current estimation. A study of sea surface currents from SST data is lacking in Indonesian seas, and more repetition is required. As a result, This method has the potential can be employed to observe aquatic environments in other Indonesian areas.